Surveillance of rotavirus diarrhea - Titis Widowati; Yati Soenarto; Achirul Bakrie; Hera Nirwati (Indonesian Pediatric Society Publishing House, 2012)
Background Rotavirus is a major cause of severe diarrhea and dehydration in children worldwide. Data on the burden of disease in Indonesia is limited. Objective To provide an epidemiological profile of rotavirus infection among children hospitalized for diarrhea in Mohammad Hoesin Hospital, Palembang. Methods In January- December 2006, a prospective, hospitalbased surveillance was carried out in children aged less than five years, presenting with diarrhea. Stool samples were examined for rotavirus using enzyme immunoassay (EIA). G- and P-typing were performed on specimens confirmed to be positive by EIA. Results A total of 513 fecal specimens from 534 children were tested for rotavirus. Rotavirus was detected in 64% of the specimens, mostly of the G9 type (62.5%). Incidence ofrotavirus diarrhea was highest in the 6 month to 2 years age group (60.4%). Children with rotavirus diarrhea were more likely to present with dehydration, compared to those with non-rotavirus diarrhea (94% vs 70%, respectively, P=0.03). Conclusion Rotavirus was the most common pathogen found in children with diarrhea. Rotavirus was detected in 64% of pediatric diarrheal specimens tested in our study. This finding warrants the use of a large-scale program to prevent disease, such as vaccination against rotavirus. [Paediatr lndones. 2012;52:22-7].